Design of Web-Based Accounting Information System for Umrah Registration and Religious Tourism Using Mysql Database at PT Nusantara Teguh Berkah - Ridwan Mansur Hidayat; Perwito Perwito; Rini Suwartika Kusumadiarti (Jurnal Computech & Bisnis (e-Journal), 2023)
The development of computer systems in information technology is increasingly rapid and accurate with the times. Cash receipts are essential in an organization, institution, or line of business. The importance of having internal control procedures for cash receipts is very beneficial for the progress and interests of the company. In this case, the company made arrangements for the cash receipts accounting system, which included registration, filing of pilgrims, down payment and settlement, and making payment reports. In addition, there are features of the latest news and procedures for worship that can help worshipers access the latest information. So at this time, an accounting information system is needed in the process of cash receipts and registration of pilgrims at PT Nusantara Teguh Berkah. This system was designed using PHP and MySQL using the Waterfall Method. Because it is web-based, this system can be accessed anywhere and anytime using a laptop or smartphone. The results obtained from designing this system are to make it easier for the admin to manage cash receipts and congregation registration from manual to digital processes.